The relevance of physical library: a case of non-resident students in Universiti Teknologi Mara, Johor - Rahimah Mohamed Yunos,; Musmailina Mustafa Kamal,; Normala Sulaiman,; Ahmad Marzuki Amiruddin Othman, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
This study investigates Universiti Teknologi Mara Cawangan Johor (UiTMCJ) non-resident (NR) students’ attitude in utilising UiTM Johor’s library resources in the year 2015. Questionnaires were distributed to a total of 100 NR students on the basis of availability to identify the frequency of their visit and the utilisation of library resources in terms of its usefulness and value. The result reveals that UiTM Johor’s library is underutilized and amongst the top three reasons chosen by the respondents were reading and borrowing books, preparing for exam and spending free time. The implication of this study would enable UiTM Johor’s library to better understand the perception of students towards them and what needs to be done to better serve the university’s community. By improving its services, this would enhance the relevance and utilization of libraries to meet the changes in demand of the students as well as the changes in the library’s function over time.